Familial multiple naevi flammei. Issue 2 (April 1984) - Shuper, A; Merlob, P; Garty, B; Varsano, I
Abstract : The third family with multiple naevi flammei and the first description of its occurrence in unidentical twins is presented. Autosomal dominant inheritance is confirmed.